The human gut microbiome in early-onset type 1 diabetes from the TEDDY study. (25th October 2018) - Vatanen, Tommi; Franzosa, Eric; Schwager, Randall; Tripathi, Surya; Arthur, Timothy; Vehik, Kendra; Lernmark, Åke; Hagopian, William; Rewers, Marian; She, Jin-Xiong; Toppari, Jorma; Ziegler, Anette-G.; et al.
Abstract Type 1 diabetes (T1D) is an autoimmune disease that targets pancreatic islet beta cells and incorporates genetic and environmental factors1, including complex genetic elements2, patient exposures3 and the gut microbiome4 . Viral infections5 and broader gut dysbioses6 have been identified as potential causes or contributing factors; however, human studies have not yet identified microbial compositional or functional triggers that are predictive of islet autoimmunity or T1D. Here we analyse 10, 913 metagenomes in stool samples from 783 mostly white, non-Hispanic children. The samples were collected monthly from three months of age until the clinical end point (islet autoimmunity or T1D) in the The Environmental Determinants of Diabetes in the Young (TEDDY) study, to characterize the natural history of the early gut microbiome in connection to islet autoimmunity, T1D diagnosis, and other common early life events such as antibiotic treatments and probiotics. The microbiomes of control children contained more genes that were related to fermentation and the biosynthesis of short-chain fatty acids, but these were not consistently associated with particular taxa across geographically diverse clinical centres, suggesting that microbial factors associated with T1D are taxonomically diffuse but functionally more coherent. When we investigated the broader establishment and development of the infant microbiome, both taxonomic and functional profiles were dynamic and highly individualized, and dominated in the first year of life by one of three largely exclusiveBifidobacterium species (B. bifidum, B. breve orB. longum ) or by the phylum Proteobacteria. In particular, the strain-specific carriage of genes for the utilization of human milk oligosaccharide within a subset ofB. longum was present specifically in breast-fed infants. These analyses of TEDDY gut metagenomes provide, to our knowledge, the largest and most detailed longitudinal functional profile of the developing gut microbiome in relation to islet autoimmunity, T1D and other early childhood events. Together with existing evidence from human cohorts7, 8 and a T1D mouse model9, these data support the protective effects of short-chain fatty acids in early-onset human T1D. An analysis of more than 10, 000 metagenomes from the TEDDY study provides a detailed functional profile of the gut microbiome in relation to islet autoimmunity, and supports the protective effects of short-chain fatty acids in early-onset type 1 diabetes.